(untitled) (Journal of the College of Basic Education, 2022)
The objective and intellectual value of the research stems from an essential point, which is that smart fabrics are fabrics with integrated functions that perform different functions that are completely different from the performance value defined by protection from environmental conditions and self-expression, but they are fabrics with advanced performance capabilities that do what ordinary cloth does, As well as performance formulas with different directions and different shapes. Hence, the aesthetic value stems from the ability of these fabrics to protect from environmental conditions and self-expression, as well as from the performance nature they provide as functions carried out by the fabric. Therefore, the aesthetic dimensions were determined between what is formal and has visible dimensions, and what is an aesthetic value stemming from the function provided by the cloth.